THE EFFECTIVENESS OF REALISTIC MATHEMATICS EDUCATION TO IMPROVE STUDENT’S PROBLEM SOLVING SKILLS IN ELEMENTARY SCHOOLS: LITERATURE REVIEW - Aulia Kholifatul Khasanah; Wiryanto; Tatag Yuli Eko Siswono (Jurnal Cakrawala Pendas, 2025)
This literature review examines the effectiveness of Realistic Mathematics Education (RME) in enhancing problem-solving skills among elementary students. The study is motivated by the persistent challenge of improving students' ability to apply mathematical concepts in real-world scenarios, a critical competency in primary education that traditional methods often fail to develop. The objective of the study is to analyze how numerous RME’s context-based approach studies impacts students' ability to understand and apply mathematical concepts in real-world scenarios. Method: Utilizing a systematic review of recent experimental and quasi-experimental studies, this study synthesizes findings from experimental and quasi-experimental research published in the past 10 years. Data were collected through structured searches in academic databases, followed by thematic analysis to compare the impact of RME and convetional mathematics instruction on student outcomes. Results Results indicate that RME consistently outperforms conventional methods, significantly improving students' problem-solving abilities by fostering a deeper understanding of math through relatable, real-life applications. RME’s emphasis on autonomy and critical thinking further contributes to student engagement and resilience, helping young learners approach complex problems with confidence and creativity. Novelty: The novelty of this review lies in its focus on elementary education, where RME's effectiveness is particularly impactful as it aligns with developmental learning stages. These findings highlight RME as a promising instructional model for strengthening foundational problem-solving skills, with implications for curriculum development and teacher training in primary education.